2019
DOI: 10.1007/s12105-019-01049-7
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of Non-Salivary Gland Neoplasms in Patients with Warthin Tumor: A Study of 73 Cases

Abstract: Warthin tumor is the second most common benign parotid neoplasm. Its association with non-salivary gland neoplasms has been sporadically reported. We reviewed clinical records of Warthin tumor diagnosed on aspiration cytology and surgical pathology to determine if there is any association with other extra-salivary gland malignant neoplasms. Computer search was made for all cases of Warthin tumor diagnosed in the parotid gland by aspiration cytology and surgical pathology at our institution between January 2007… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 59 publications
(31 reference statements)
0
5
0
Order By: Relevance
“…Several studies have failed to detect clonality of the tumor cells, and a non-neoplastic (metaplastic) process involving salivary inclusions within intraparotid lymph nodes has been postulated as a pathogenetic explanation of WTs [ 10 , 11 ]. The metaplastic theory has been linked to the effect of chronic cigarette smoking, a factor that has also been proposed to explain the striking historical male predominance and the higher frequency of associated head and neck squamous cell carcinoma in patients with WTs [ 12 ]. Irrespective of the exact etiology, damage to mitochondrial DNA, possibly resulting from chronic nicotine abuse, and mitochondrial abnormalities including mitochondrial enzyme dysregulations seem to play a role in the morphogenesis of WTs [ 13 , 14 ].…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have failed to detect clonality of the tumor cells, and a non-neoplastic (metaplastic) process involving salivary inclusions within intraparotid lymph nodes has been postulated as a pathogenetic explanation of WTs [ 10 , 11 ]. The metaplastic theory has been linked to the effect of chronic cigarette smoking, a factor that has also been proposed to explain the striking historical male predominance and the higher frequency of associated head and neck squamous cell carcinoma in patients with WTs [ 12 ]. Irrespective of the exact etiology, damage to mitochondrial DNA, possibly resulting from chronic nicotine abuse, and mitochondrial abnormalities including mitochondrial enzyme dysregulations seem to play a role in the morphogenesis of WTs [ 13 , 14 ].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, because smoking is an identical risk factor for lung cancer ( 2 ) and Warthin’s tumor ( 37 ), lung cancer coexisting with Wartin’s tumor is not puzzling ( 38 – 41 ). It is reported that there is a significant correlation between the occurrence of parotid gland warthin’s tumor and lung cancer ( 38 , 42 ). About 19% of patients with warthin’s tumor in parotid gland also have lung cancer ( 38 ).…”
Section: Discussionmentioning
confidence: 99%
“…Pain can be present in some WT patients, especially when the tumor is compressed. However, with regard to pain, one should keep in mind that the tumor may represent another type of salivary gland tumor or could be malignant, which is more likely to cause this symptom [4]. Finally, some patients clearly prefer to have their WT removed because of persistent fear of an underlying malignancy.…”
Section: Primary Surgical Excisionmentioning
confidence: 99%
“…Around 15% of WTs are multifocal in the same gland and in approximately 10% of cases are present bilaterally [1,3]. WTs have been reported in association with other salivary gland neoplasms (benign and malignant) [4]. It has also been reported that WTs arise in intra-and periparotid lymph nodes and may account for the diagnosis of the WT-isolated extraparotid gland in the neck [1,5].…”
Section: Introductionmentioning
confidence: 99%